Effect of Laser Power on the Microstructure and Fracture of Notched IN718 Specimens Fabricated by Laser Powder Bed Fusion - Naheen Ibn Akbar; Kalyan Nandigama; Ishaan Sati; Bharath Bhushan Ravichander; Golden Kumar (Metals, 2025)
This study examines the impact of laser power on the microstructure and fracture behavior of IN718 specimens fabricated using laser powder bed fusion. Single-edge notched bend specimens were fabricated with varying laser power from 140 W to 260 W, and their fracture behavior was analyzed following the ASTM E1820-23b standard. The porosity and grain morphology remained unaffected by the presence of a notch parallel to the build direction. An elastic–plastic fracture mechanics approach was used to measure J-R curves, which quantify the energy required for crack propagation. Crack initiation and growth during quasistatic loading were monitored using image analysis. The results revealed a strong correlation between crack initiation and propagation, type of porosity, and relative density. The specimen printed with the optimal laser power of 180 W demonstrated the highest relative density and the greatest resistance to crack propagation. Large non-spherical defects formed due to lack-of-fusion at lower laser power are more detrimental to the crack propagation resistance.